Efficacy and safety of corticosteroid implants in non-infectious uveitis: a systematic review with network meta-analysis - Rafael José Monteiro da Silva Vieira (2020)
Background/aims: Intravitreal corticosteroid implants are used in the treatment of non-infectious uveitis, but there is little published evidence assessing and comparing these implants. The aim of this systematic review of randomized clinical trials (RCTs) was to analyse evidence regarding the efficacy and safety of intravitreal implants in non-infectious uveitis and to compare the different existent implants. Methods: We searched in five electronic databases (PubMed/Medline, Scopus, Web of Science, Cochrane Library and ClinicalTrials.gov) up to August 2019, and screened reference lists of included studies and relevant reviews. We performed network meta-analysis so that we could compare 0.18 mg fluocinolone acetonide implants, 0.70 mg and 0.35 mg dexamethasone implants, and sham procedures. Results: Eight RCTs (n = 1621 eyes) were included in this systematic review, of which three articles from two studies (assessing a total 358 patients) were included in network meta-analysis. The 0.70 mg dexamethasone implant was associated with better results than the 0.18 mg fluocinolone acetonide implant at decreasing central macular thickness variation (mean difference=-70.3μm; 95%CI=-138.5;-2.2), and with less frequently development of cataracts at 12 (RR=0.36; 95%CI=0.17;0.79) and 36 months (RR=0.37; 95%CI=0.20;0.71). No other significant differences were found between different intravitreal implants regarding efficacy or safety outcomes. Conclusions: These results suggest that, on the short term, the 0.70 mg dexamethasone implant associates with higher central macular thickness decreases, and lower risk of cataracts than the 0.18 mg fluocinolone acetonide implant. Additional RCTs with standardised outcomes are needed to directly and more accurately compare currently available corticosteroid implants for non-infectious uveitis.